Targeting the non-classical estrogen pathway in neurodegenerative diseases and brain injury disorders - Koszegi, Zsombor; Cheong, Rachel Y. (Frontiers in Endocrinology, 2022)
Estrogens can alter the biology of various tissues and organs, including the brain, and thus play an essential role in modulating homeostasis. Despite its traditional role in reproduction, it is now accepted that estrogen and its analogues can exert neuroprotective effects. Several studies have shown the beneficial effects of estrogen in ameliorating and delaying the progression of neurodegenerative diseases, including Alzheimer’s and Parkinson’s disease and various forms of brain injury disorders. While the classical effects of estrogen through intracellular receptors are more established, the impact of the non-classical pathway through receptors located at the plasma membrane as well as the rapid stimulation of intracellular signaling cascades are still under active research. Moreover, it has been suggested that the non-classical estrogen pathway plays a crucial role in neuroprotection in various brain areas. In this mini-review, we will discuss the use of compounds targeting the non-classical estrogen pathway in their potential use as treatment in neurodegenerative diseases and brain injury disorders.